What mechanisms dominate the activity of Geminid Parent (3200) Phaethon?. Issue 3 (10th November 2018) - Yu, Liang Liang; Ip, Wing Huen; Spohn, Tilman
Abstract: A long-term sublimation model to explain how Phaethon could provide the Geminid stream is proposed. We find that it would take ∼6 Myr or more for Phaethon to lose all of its internal ice (if ever there was) in its present orbit. Thus, if the asteroid moved from the region of a 5:2 or 8:3 mean motion resonance with Jupiter to its present orbit less than 1 Myr ago, it may have retained much of its primordial ice. The dust mantle on the sublimating body should have a thickness of at least 15 m but the mantle could have been less than 1 m thick 1000 yr ago. We find that the total gas production rate could have been as large as $10^{27}\rm \, s^{-1}$ then, and the gas flow could have been capable of lifting dust particles of up to a few centimetres in size. Therefore, gas production during the past millennium could have been sufficient to blow away enough dust particles to explain the entire Geminid stream. For present-day Phaethon, the gas production is comparatively weak. But strong transient gas release with a rate of ${\sim }4.5× 10^{19}\rm \, m^{-2}\, s^{-1}$ is expected for its south polar region when Phaethon moves from 0° to 2° mean anomaly near perihelion. Consequently, dust particles with radii of <∼260 μm can be blown away to form a dust tail. In addition, we find that the large surface temperature variation of >600 K near perihelion can generate sufficiently large thermal stress to cause fracture of rocks or boulders and provide an efficient mechanism to produce dust particles on the surface. The time-scale for this process should be several times longer than the seasonal thermal cycle, thereby dominating the cycle of appearance of the dust tail.